2020
DOI: 10.30699/ijp.2020.130491.2442
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in Covid-19: A Prognostic Marker for Severe Disease

Abstract: Scan to discover onlineBackground & Objective: Previous studies have addressed the electrolyte abnormalities such as hypocalcemia in COVID-19 patients. We aimed to compare the laboratory findings especially the electrolyte levels among COVID-19 patients and healthy controls and evaluate their prognostic values.Methods: This case-control study included 91 COVID-19 patients and 169 healthy individuals. Their laboratory parameters including electrolytes, albumin, liver enzymes, complete blood count, vitamin D, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
(25 reference statements)
2
25
2
Order By: Relevance
“…T lymphocytes are essential to control viral infections. 12,13,22 The results of D-dimer analysis in the present study showed that there is a direct relationship between Ddimer-dimer level and hypocalcemia. The lower the serum calcium level, the significantly higher the D-dimer level and consequently the severity of the disease.…”
Section: Selection Of Studies and Study Characteristicssupporting
confidence: 54%
See 3 more Smart Citations
“…T lymphocytes are essential to control viral infections. 12,13,22 The results of D-dimer analysis in the present study showed that there is a direct relationship between Ddimer-dimer level and hypocalcemia. The lower the serum calcium level, the significantly higher the D-dimer level and consequently the severity of the disease.…”
Section: Selection Of Studies and Study Characteristicssupporting
confidence: 54%
“…Among the meta-analysis evaluated studies, seven studies have examined serum calcium levels in healthy individuals and patients with COVID-19. 10,13,[17][18][19][20][21] Also, the relationship between mortality and hypocalcemia in eight articles evaluated, 9,12,13,[22][23][24][25][26] in addition, the relationship between severity of the disease and hypocalcaemia in seven articles evaluated, 13,22,[27][28][29][30][31] and the relationship between hypocalcaemia and the length of hospital stay and admission in the ICU is reported in four and five articles, respectively. 9,12,13,19,22,32 Also, four articles reported hypocalcaemia association with D-dimer level and six articles reported that hypocalcaemia is related to lymphocyte count.…”
Section: Selection Of Studies and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypokalemia, another complication in COVID-19, can exacerbate acute respiratory distress syndrome (ARDS) and increase the risk of heart injuries (34). Hypocalcemia has also been observed as one of the electrolytes disorders in patients with COVID 19, which if not controlled, can increase mortality rate (35). Syndrome of inappropriate antidiuretic hormone (SIADH) has been reported in some COVID-19 patients and implicated in causing fluids and electrolyte disturbances (36).…”
Section: Fluid and Electrolytes Disturbances In Covid-19mentioning
confidence: 99%